A copper electroplating formula for BVHs and THs filling at one process. Issue 3 (1st August 2016) - Liu, Jia; Chen, Jida; Zhang, Zhu; Yang, Jiali; He, Wei; Chen, Shijin
Abstract : Purpose: The purpose of this paper is to introduce a new copper electroplating formula which is able to fill blind microvias (BVHs) and through holes (THs) at one process through a direct current (DC) plating method. Design/methodology/approach: Test boards of printed circuit board (PCB) fragments with BVHs and THs for filling plating are designed. The filling plating is conducted in a DC plating device, and the filling processes and influence factors on filling effect of BVHs and THs are investigated. Dimple depths, surface copper thickness, thermal shock and thermal cycle test are applied to characterize filling effect and reliability. In addition, to overcome thickness, increase of copper on board surface during filling plating of BVHs and THs, a simple process called pattern plating, is put forwarded; a four-layered PCB with surface copper thickness less than 12 μm is successfully produced. Findings: The filling plating with the new copper electroplating formula is potential to replace the conventional filling process of BVHs and THs of PCB and, most importantly, the problem of thickness increase of copper on board surface after filling process is overcome if a pattern plating process is applied. Research limitations/implications: The dimple depth of BVHs and THs after filling plating is not small enough, though it meets the requirements, and the smallest diameter and largest depth of holes studied are 75 and 200 μm, respectively. Hence, the possibility for filling holes of much more small in diameter and large in depth with the plating formula should be further studied. Originality/value: The paper introduces a new copper electroplating formula which achieves BVHs and THs filling at one process through a DC plating method. It overall reduces production processes and improved reliability of products resulting in production cost saving and production efficiency improvement.